Applying Predictive Analytics for Resource Allocation in Islamic Educational Organizations: Enhancing Efficiency and Decision-Making through AI - Efrita Norman; Arman Paramansyah; Dessy Damayanthy; Lina Marliani (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to fill the knowledge gap and identify opportunities for the application of AI in resource management in IEOs. This research shows that the adoption of predictive analytics technology in Islamic educational institutions has great potential, but there are challenges to overcome. In the context of urban areas, these technologies can be integrated more easily due to better infrastructure and adequately skilled staff. This is in line with previous research which shows that infrastructure and training are key factors in the successful implementation of new technologies in educational settings. This study used a quantitative and qualitative approach (Moxed Methods). Qualitative data analysis techniques through several techniques, namely, surveys, interviews, participant observation and documentation. Quantitative data analysis techniques through several techniques, namely statistical methods, thematic, document analysis, validity and reliability tests.